THE EFFECTOR FUNCTIONS OF MACROPHAGES TRANSFECTED WITH INTERFERON- GAMMA GENE MEDIATED BY RECOMBINANT ADENOVIRUS1 - Lei, Hong; Cao, Xuetao; Yu, Yizhi; Chen, Guoyou; Zhang, Minghui (Chinese Journal of Cancer Research, 2013)
Macrophages(M∅s) are not only a kind of immune effector cells but also a kind of antigen-presenting cells(APC). In order to improve their antitumor effect, we transfected interferon-gamma(IFN-γ) gene into M∅s by recombinant adenovirus because IFN-γ is a kind of potent macrophage-activating factor(MAF). High level of IFN-γ could be detected in the supernatants of Mq∅s after IFN-γ gene transfection and IFN-γ secretion peaked at 20 hour. The cytotoxicity of IFN-γ genetransfected M∅s increased significantly. The secretion of TNF, IL-1, nitric oxide(NO) also increased to some extent. The results demonstrated that recombinant adenovirusmediated IFN-γ gene transfection could improve the effector functions of M∅s efficiently.